Camelids: new players in the international animal production context - Zarrin, M. (2021)
The Camelidae family comprises the Bactrian camel (Camelus bactrianus), the dromedary camel (Camelus dromedarius), and four species of South American camelids: llama (Lama glama), alpaca (Lama pacos) guanaco (Lama guanicoe), and vicuña (Vicugna vicugna). The main characteristic of these species is their ability to cope with either hard climatic conditions like those found in arid regions (Bactrian and dromedary camels) or high-altitude landscapes like those found in South America (South American camelids). Because of such interesting physiological and adaptive traits, the interest for these animals as livestock species has increased considerably over the last years. In general, the main animal products obtained from these animals are meat, milk, and hair fiber, although they are also used for races and work among other activities. In the near future, climate change will likely decrease agricultural areas for animal production worldwide, particularly in the tropics and subtropics where competition with crops for human consumption is a major problem already. In such conditions, extensive animal production could be limited in some extent to semi-arid rangelands, subjected to periodical draughts and erratic patterns of rainfall, severely affecting conventional livestock production, namely cattle and sheep. In the tropics and subtropics, camelids may become an important protein source for humans. This article aims to review some of the recent literature about the meat, milk, and hair fiber production in the six existing camelid species highlighting their benefits and drawbacks, overall contributing to the development of camelid production in the framework of food security